2013
DOI: 10.1172/jci64535
|View full text |Cite
|
Sign up to set email alerts
|

KDM2B promotes pancreatic cancer via Polycomb-dependent and -independent transcriptional programs

Abstract: Epigenetic mechanisms mediate heritable control of cell identity in normal cells and cancer. We sought to identify epigenetic regulators driving the pathogenesis of pancreatic ductal adenocarcinoma (PDAC), one of the most lethal human cancers. We found that KDM2B (also known as Ndy1, FBXL10, and JHDM1B), an H3K36 histone demethylase implicated in bypass of cellular senescence and somatic cell reprogramming, is markedly overexpressed in human PDAC, with levels increasing with disease grade and stage, and highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
163
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(172 citation statements)
references
References 48 publications
(86 reference statements)
6
163
2
1
Order By: Relevance
“…5 In addition, IMP2-positive glioma and PPARGC1A (PGC1a)-positive melanoma showed tumor progression associated with mitochondrial energy activation in the absence and presence of enhanced ROS levels, respectively. 39,40 Thus, despite the general enhancement of glycolytic bioenergetic requirements in many cancers (so called as "Warburg effect"), several recent studies have revealed unanticipated tumor metabolism by Warburg, that is, the bioenergetic type of tumors can vary widely from glycolysis to OXPHOS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5 In addition, IMP2-positive glioma and PPARGC1A (PGC1a)-positive melanoma showed tumor progression associated with mitochondrial energy activation in the absence and presence of enhanced ROS levels, respectively. 39,40 Thus, despite the general enhancement of glycolytic bioenergetic requirements in many cancers (so called as "Warburg effect"), several recent studies have revealed unanticipated tumor metabolism by Warburg, that is, the bioenergetic type of tumors can vary widely from glycolysis to OXPHOS.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with the upregulation of FBXL10 in human leukemia and solid tumors, [3][4][5][6] selective inhibition of FBXLl10 may be a therapeutic strategy to achieve improvement in these diseases. Figure 7.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations